Impact of Internet Banking on Customer Satisfaction: A Case Study of State Banks in Kandy District - Kodithuwakku, Ms. Sujeewa (Academy of Social Science Journal, 2018)
In the Sri Lankan context the banking sector has a major role of regulating the financial needs of the society. Almost all of the retail financial needs of the general public are fulfilled by the banks in Sri Lanka. Nowadays the implementation of sophisticated technology in the banking sector drives the financial activities to the green banking concept providing more convenience to the customers with a busy lifestyle. Internet banking is one of these facilities provided by the bankers in the 1980sâ€™. But it is not yet well established in the Sri Lankan society. The main objective of the research was to identify the impact of internet banking in state banks on customer satisfaction by considering technology based factors, transaction based factors and demographic factors related to internet banking. 1500 residents in Peradeniya, Gannoruwa, Mulgampola and Heerassagala in the Kandy district who were belonging to the personal banking customer category with internet banking experience were selected as the sample by using convenient sampling method. The primary data collection was done by a questionnaire administration among a sample and face interviews were done as a method of primary data collection while the secondary data collection was done by referring the banking publications and web sites. Data analysis was done using both descriptive and quantitative methods. The Spearman’s Correlation Coefficient was used to evaluate the impact of technology based factors on customer satisfaction. The study found that there is an impact of demographic factors to the internet banking on customer satisfaction while both transactions based factors and technology based factors has a positive correlation with the customer satisfaction on internet banking facility. On the other hand it was proved that there is an impact of internet banking facility on overall customer satisfaction too.